Atlantic Grey Seal Milk Shows Continuous Changes in Key Metabolites and Indicators of Metabolic Transition in Pups From Birth to Weaning - Watson, David G.; Pomeroy, Patrick P.; Kennedy, Malcolm W. (Frontiers in Marine Science, 2021)
Mothers of the Atlantic grey seal, Halichoerus grypus, lactate for about 20 days, during which they do not feed and may have no access to water. Following weaning, they depart to sea leaving their pups unattended and unfed for up to another 40 days. We are interested in how this lactation strategy supports the pups’ rapid growth and development while also preparing them for their long fast before independently going to sea. We report a broad spectrum metabolomic analysis of whole milks of these seals that reveals continuous changes in key metabolites from birth to weaning. Certain components exhibit abbreviated appearances at the onset of lactation, followed by continuous rises or falls in others until weaning. Riboflavin/Vitamin B2, hormone-related sterol sulfates, lactose, and complex oligosaccharides all appear in milk briefly after birth then disappear. Lipids associated with cellular signaling and brain development occur at highest levels shortly after birth, then diminish. In contrast, other lipids and Vitamin B6/pyridoxine steadily increase as weaning approaches. Overall, these findings may indicate an early transition from carbohydrate to fat-based energy metabolism and establishment of gut microbiomes in pups, followed by provisioning for post-weaning development and fasting.